PELATIHAN MENENDANG BOLA DENGAN KONSEP GERAK PARABOLA - Darmawan Harefa; Tatema Telaumbanua; Efrata Gee; Kalvintinus Ndruru; Fatolosa Hulu; Lies Dian Marsa Ndraha; Mastawati Ndruru; Murnihati Sarumaha (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
The philosophy of the game of football begins with a question of why and how the phenomenon in football can occur in terms of physics. In soccer, there are some interesting phenomenon, such as banana kicks. Botohilisilambo Village is a village located in the Luahagundremaniamolo sub-district, South Nias Regency. Didesa botohili silambo has the only good field for sports facilities for soccer. Every Sunday this field is filled with you young and old, who want to channel a hobby to simply play ball without technique. There, young people are not familiar with the technique of kicking a good and perfect ball. So try to introduce to young people in the village of Botohili Silambo field to try to do the technique of kicking the ball with the concept of parabolic motion when kicking both during long distance shots and in the penalty area. This benefit to train makes it easy for them to kick the ball with the basic technique of long-distance kicks in curved curves into the air.